2010
DOI: 10.1029/2010gl044555
|View full text |Cite
|
Sign up to set email alerts
|

How much can the vertical distribution of black carbon affect its global direct radiative forcing?

Abstract: [1] Black carbon (BC) has an increased forcing per unit mass when it is located above reflective clouds. To explore sensitivity of forcing to aerosol vertical location, we used a column radiative transfer model to produce globally-averaged values of normalized direct radiative forcing (NDRF) for BC over and under different types of clouds. We developed a simple column-weighting scheme based on the mass fractions of BC that are over and under clouds in measured vertical profiles. The resulting NDRF is in good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 42 publications
4
136
0
1
Order By: Relevance
“…That estimate includes both a gross 15 % global downscaling of BC forcing efficiency due to overestimation of BC aloft, and a differentiated regional upscaling of emissions derived by comparing aerosol absorption optical depth from AeroCom Phase I with that from AERONET ground-based remote sensing. Their downscaling, based on recent model studies (Bond et al, 2013;Samset and Myhre, 2011;Zarzycki and Bond, 2010) and evaluation of AeroCom Phase I results (Schwarz et al, 2010), is comparable to our 25 % reduction in forcing, though our reduction is attributed to remote ocean areas. For near-source and remote regions covered in the present study we here find no need for an emission bias-related upscaling; however the present data do not cover the regions where the upscaling in that analysis (Bond et al, 2013) was most pronounced.…”
Section: Consequences For Modelled Bc Ff + Fb Rfmentioning
confidence: 58%
See 1 more Smart Citation
“…That estimate includes both a gross 15 % global downscaling of BC forcing efficiency due to overestimation of BC aloft, and a differentiated regional upscaling of emissions derived by comparing aerosol absorption optical depth from AeroCom Phase I with that from AERONET ground-based remote sensing. Their downscaling, based on recent model studies (Bond et al, 2013;Samset and Myhre, 2011;Zarzycki and Bond, 2010) and evaluation of AeroCom Phase I results (Schwarz et al, 2010), is comparable to our 25 % reduction in forcing, though our reduction is attributed to remote ocean areas. For near-source and remote regions covered in the present study we here find no need for an emission bias-related upscaling; however the present data do not cover the regions where the upscaling in that analysis (Bond et al, 2013) was most pronounced.…”
Section: Consequences For Modelled Bc Ff + Fb Rfmentioning
confidence: 58%
“…The uncertainty ranges (5-95 %) show that BC is still a major contributor to the total uncertainty on anthropogenic RF. Further, it has recently been shown that, because the direct RF per unit mass BC increases strongly with altitude (Ban-Weiss et al, 2011;Zarzycki and Bond, 2010;Samset and Myhre, 2011), the diversity in modelled vertical profiles of BC concentration in the AeroCom Phase II models may account for up to 50 % of the model diversity in anthropogenic BC RF . Climate model simulations, however, indicate that, while direct BC forcing strengthens with altitude, its climate efficacy may decrease, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Further analyses are planned. Within the framework of the AeroCom Phase II intercomparison (Myhre et al, 2012), it will be interesting to investigate issues like the regional responses to anthropogenic aerosol forcing, and modeling uncertainties in the distribution and absorption properties of black carbon (Zarzycki and Bond, 2011;Samset and Myhre, 2011;Stier et al, 2007).…”
Section: Direct Radiative Effect Of Aerosolsmentioning
confidence: 99%
“…Langner and Rodhe, 1991;Feichter et al, 1996) gradually led to appreciation of the importance of microphysics in aerosol modelling. The newer models have thus included more detailed descriptions of aerosol composition and size distribution, using different approaches (Wilson et al, 2001;Jacobson, 2001;Vignati et al, 2004;Easter et al, 2004;Stier et al, 2005;Spracklen et al, 2005;Liu et al, 2005;Bauer et al, 2008;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diversity in existing estimates of the climate effect of BC is large (Bond et al, 2013;Boucher et al, 2013;Myhre et al, 2013). The causes for the diversity in estimates are many, from emissions (Amann et al, 2013;Cohen and Wang, 2014;Lam et al, 2012;Stohl et al, 2013;Wang et al, 2014b), lifetime and abundance (Hodnebrog et al, 2014;Samset et al, 2014;Wang et al, 2014a) to radiative efficiency Zarzycki and Bond, 2010).…”
Section: Introductionmentioning
confidence: 99%